Studi Kepustakaan Pengaruh Suplementasi Madu dalam Pengencer Terhadap Kualitas Semen Ayam - Yosefina T. Sukanto; Nancy D. F. K. Foeh; Tarsisius Tophianong (Jurnal Veteriner Nusantara, 2023)
Honey is a thick, sweet-tasting liquid containing about 70-80% natural sugars, minerals, vitamins and enzymes. The content of 65% sugar is in the form of simple monosaccharides (fructose, glucose and sucrose). The high sugar content in honey can be used as a source of nutrients besides honey also acts as an antioxidant. This study aims to determine the antioxidants and other active substances in honey so that their addition to the diluent can maintain the quality of chicken semen during storage. This literature study was carried out through searching and collecting various literatures using Google Schoolar and PubMed then arranged using Mendeley. Sources of literature are scientific journals, scientific articles, Ebooks and seminar proceedings with "keywords" the effect of honey supplementation in diluent on the quality of chicken semen. Based on the results of the study, kalliandra honey is one of the best alternatives as antioxidants in chicken semen diluents, while the best honey level is 2%. The content of antioxidants such as vitamin C, vitamin E and flavonoids in honey protects the sperm cell membrane of danger coldshock (cold shock), in addition to fructose and glucose can be made as a source of nutrients for spermatozoa during storage. The addition of honey in feed can improve the quality of chicken semen because it contains the minerals Zn (zinc), Se (selenium) and vitamins (E and C) which help in the process of spermatogenesis.